Smart medicine dispenser with online dispensing capabilities - Castillo, John Joseph M. (Animo Repository, 2021)
As healthcare is known as one of the most crucial factors in defining people in a certain vicinity it is of importance to have an approach that is linear to the technological advancements to preserve and provide utmost efficiency. One of the most common medicinal errors is the patient’s delayed medicine intake due to the effects of old age and patient caregivers having to memorize the timing of each dose. The compensation of these lacking areas is lifted by the Smart Medicine Dispenser with Offline Dispensing Capabilities. This concept would essentially be able to eliminate delayed and inconvenient medicine intake as it allows the patient or caregiver to access the device manually through the keypad and remotely through Wi-Fi. The remote access feature of the smart medicine dispenser, allows the caregiver to administer the timing of the patient’s medication without having to be near the patient.